Body.: Illness, Memory, and the Dynamics of Healing - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
When residents of Chimoio and Honde talk of the forceful and potentially perilous dimensions of spirits, healing, and illness, they frequently relate them to tchianhu wo atewe. Spirits, which embody various potencies and capacities, are integral to diurnal and nocturnal lives in urban and rural contexts alike. As shown previously, a wide range of spirits exhibit dynamics of re-/deterritorialization. Further, people relate to ancestral spirits, so-called vadzimu, in annual private rituals to secure the well-being of their dzindza and household, or they participate in more elaborate communal rituals led by authorities like the tchirenge, who invoke the ancestors’ protection from
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Conclusion.: Uncapturability, Dynamics, and Power - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Ethnography harbors the power of critique—political, social, and theoretical. Ultimately a capacity to destabilize, this orientation also applies when writing an account of the violence inherent to processes of state formation in Mozambique. While such critical potential may be realized in a number of ways, here I have privileged perspectives forged on the margins of the centers of power, supplemented by historical sources. But there is more to it than this: by privileging a decentering of institution-based notions of the state informed by multiple readings of Deleuze, a wholly different picture of what a state is—and might be
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Economy.: Substance, Production, and Accumulation - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
In After Kinship (2004), Janet Carsten employs “substance” to delineate important dimensions of classical understandings of kinship and personhood. She does so by reinterpreting Schneider’s (1980) studies on American kinship and revisiting Marilyn Strathern’s (1988) analyses of Trobriand kinship and in/dividuality. Based on these reinterpretations and, more generally, extensive comparisons between Indian, Melanesian, British, and American cases, Carsten specifically recontextualizes and questions the components of kinship as code and substance as argued by Schneider. Concentrating on substance, she argues that the term has a range of different connotations but is used in diverse ways, ranging from the stuff of relations
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Law.: Political Authority and Multiple Sovereignties - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Since the General Peace Agreement was signed in 1992 the legal, administrative, and political sectors of Mozambique have undergone multiple reforms that have exposed the complexity of its historical trajectories of law, violence, and authority. From the perspective of those living in the impoverished and frequently dangerous and violent urban and peri-ur-ban bairros, a great variety of agencies and authorities can be approached at times of difficulty or trouble. These range from n’angas, profetes, and police agents to government bureaucrats and Frelimo secretaries. This chapter explores the general situation in the marginalized communities making up the rural-urban continuum of Chimoio
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Sovereignty.: The Mozambican President and the Ordering of Sorcery - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Why does the Mozambican state attempt to control uroi —a force that is seemingly incompatible with the state rationale of both the postindependence Afro-Marxist era as well as the post–civil war period of neoliberal democracy? This chapter will broach this question through untangling the problematic relations between spirit and state within the context of AMETRAMO (Associação da Medicina Tradicional de Moçambique —the Association for Traditional Medicine in Mozambique), a state-sanctioned institution organizing so-called traditional healers. I will argue that the case of AMETRAMO exemplifies a statal mechanism for capture and control of the force fields and potencies of the
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Spirit.: Chiefly Authority, Soil, and Medium - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
This vision of sovereign power hovering above the relations between natural and human elements is relevant beyond genealogical analyses of biopower, pastoral power, and govenmentality. If we go beyond Foucault’s near exclusive context and subject of enquiry, Europe, these relations move to the forefront of social and political life. In Honde, crucial interconnections between polities of chiefly rule and traditional authority, cosmologies of land and the well-being of its inhabitants, and soil are present in a number of contexts. We have seen indications of this previously through Renamo’s appropriation of the traditional field, in Ngungunyane’s problematic relations with rainmaking capacities,
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Territory.: Spatio-Historical Approaches to State Formation - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
What does the notion of territory entail for state formation? As Elden (2013) has made clear in his recent genealogy of territory, it may be seen as a spatial extension of state power. While Elden’s point is crucial, in this chapter I will entertain the idea that the colonial state form is not different in its key dynamics from later state forms, as well as certain African polities, and in this way the chapter challenges the idea of the colonial state as radically different from earlier or later state forms. While basing myself on information from Manica Province, the empirical
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Violence.: War, State, and Anthropology in Mozambique - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
How is one to make sense of state formation as a predominantly violent process? More concretely, how is one, as an anthropologist, to understand one’s interlocutors’ repeated insistence on life being a sustained period of suffering ( sofrimento )? One point at which to start is with the most recent large-scale period of violence, namely the Mozambican civil war (1976–92). During this phase of violent upheaval, the traditional field was implicated in complex ways and its reality as a domain of the potential was actualized in various manners vis-à-vis state dynamics and war machine dynamics. By describing the civil war as
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Corporate Social Responsibility in Mozambique - Kaufmann, Friedrich; Simons-Kaufmann, Claudia (Corporate Social Responsibility in Sub-Saharan Africa: Sustainable Development in its Embryonic Form, 2016)
Mozambique is a young African country with a strong growing economy and increasing foreign direct investment. We can observe a rising number of Corporate Social Responsibility (CSR) projects and activities in the country. Nevertheless there is still no systematic approach or coordination through public authorities or the business sector itself. CSR is mainly motivated by immediate own company needs like training or health of workers. We also find philanthropy projects as well as projects supporting local communities on development priorities, mainly health, education and community development. CSR, as part of a business concept, is mainly limited to large companies and foreign investors with international experience and less to small and medium-sized enterprises (SMEs). Many national companies, especially SMEs still do not have the CSR capacity or the respective mind set. First of all it is the mega projects that have their professional CSR departments and budgets. In the mining sector a CSR component is now compulsory by law since 2014.As public institutions are weak, CSR in Mozambique is more about “CSR towards compliance” and sometimes less about “CSR beyond compliance”. Strong views are expressed by civil society that for example the enforcement of labour legislation within companies is weak and hardly controllable by the government. This fact combined with corruption issues makes CSR towards compliance of existing labour, environmental, fiscal laws and other regulation an important topic. Nevertheless it is questionable if this should be considered as CSR. CSR in general is sometimes seen as “green washing” by big investors, benefitting on the other hand from generous tax exemptions and special deals with the government. Nevertheless, CSR is of growing importance in Mozambique and as the new mining CSR law shows, government is slowly entering the CSR landscape. A better coordination and public-private dialogue about CSR is necessary in order to make it a more useful and an efficient instrument for development. Nevertheless it should be clear that CSR is voluntary and in a globalized economy with international value chains becomes more and more an international issue.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado